Metal free mild and selective aldehyde cyanosilylation by a neutral penta-coordinate silicon compound - Swamy, V. S. V. S. N.; Bisai, Milan Kumar; Das, Tamal; Sen, Sakya S. (Chemical Communications, 2017)
This study demonstrates the preparation and structural characterization of a Si(IV) hydride (PhC(NtBu)(2)SiH(CH3)Cl) (1) and its use as a catalyst for the cyanosilylation of a variety of aldehydes. Compound 1 represents the first neutral penta-coordinate silicon(IV) species that catalyzes cyanosilylation of aldehydes under mild conditions.

Monomeric magnesium catalyzed alkene and alkyne hydroboration - Kumar, Rohit; Dutta, Sayan; Sharma, Vishal; Singh, Praval P.; Gonnade, Rajesh G.; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2022)
In this work, two monomeric magnesium alkyl complexes (1 and 2) were prepared using bis(phosphino)carbazole framework and among them 1 has been used as a catalyst for hydroboration of alkenes and alkynes with pinacolborane (HBpin). A broad variety of aromatic and aliphatic alkenes and alkynes were efficiently reduced. Anti-Markovnikov regioselective hydroboration of alkenes and alkynes was achieved, which was confirmed by deuterium-labelling experiments. The work represents the first example of the use of magnesium in homogeneous catalytic hydroboration of alkene with broad substrate scope. Experimental mechanistic investigations and DFT calculations provided insights into the reaction mechanism. Finally, the hydroboration protocol was extended to terpenes.
Keywords: carbazole; Magnesium; monomeric complexes; phosphorous; X-ray Structure

Magnesium-catalyzed primary, secondary, and tertiary amide hydroboration - Mahata, Biplab; Devaraj, V.; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2025)
Catalytic hydroboration of amides is highly important because the resultant amines are commonly found in natural products, pharmaceuticals, agrochemicals, dyes, and other applications. In comparison to the conventional reduction of amides using (over)stoichiometric reductants, hydroboration of amides using magnesium compounds represents a green and sustainable approach because magnesium is both Earth abundant and environmentally benign. However, there is only one report on magnesium-catalyzed deoxygenative hydroboration of secondary and tertiary amides. Here, we describe the synthesis and structural authentication of two new magnesium compounds (1 and 2) featuring a flexible PNP ligand and the utilization of 2 as a catalyst for the pinacolborane-mediated reduction of primary, secondary, and tertiary amides to amines. The reaction scope is explored, and a mechanism is proposed based on experimental and theoretical insights.

Magnesium-ligand cooperation in breaking the O-H and C-H bonds of water and diazoalkane - Sharma, Vishal; Dash, Soumya Ranjan; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2025)
In our previous paper, we reported that the reaction of a tridentate nacnac ligand with a pendant picolyl group, with KHMDS and MgI2, resulted in the formation of a homoleptic hexacoordinate magnesium compound. Here, we show that the analogous reaction of the ligand with CH3MgBr led to a heteroleptic magnesium bromide species (1). Attempts to generate the magnesium hydride species from 1 led to the dearomatization of the pyridine ring, and the resulting product was a magnesium hydroxide (3) presumably generated due to an adventitious amount of water. The reaction of the ligand with nBu2Mg afforded a unique dearomatized magnesium species (2) in high yield. Theoretical calculations reveal the presence of a nonbonding orbital on the magnesium, susceptible to nucleophilic attack. Indeed, the reaction of 2 with H2O/D2O cleaves the O-H/D bond via magnesium-ligand cooperation and generates a magnesium hydroxide (4 and 5). In addition, 2 reacts with Me3SiCHN2 and cleaves the C-H bond to generate another unusual, well-defined magnesium compound with a bridging isocyanide moiety (6) via migration of the SiMe3 group from the carbon to the nitrogen atom. The latter can be described as a dimer of magnesium isocyanamide. DFT calculations were performed to understand the electronic structures of the synthesized molecules.

Manganese(i)-catalyzed dehydrogenative borylation of terminal alkynes - Ghanwat, Pratiksha B.; Bora, Debashree; Pandya, Rinu; Vanka, Kumar; Saha, Biswajit; Sen, Sakya S. (Dalton Transactions, 2025)
Compounds containing carbon-boron bonds serve as valuable intermediates for constructing more complex molecules by transforming these bonds into other carbon-element bonds. The catalytic dehydrogenative borylation of carbon-hydrogen bonds using HBpin presents an appealing method for synthesizing carbon-boron bonds. While this approach has been extensively explored with noble metals for various types of carbon-hydrogen bonds, its application with manganese-based catalysts remains rare. This study explores a dehydrogenative borylation process employing an Earth-abundant transition metal catalyst, FcbpyMn(CO)3Br (Mn(i)), in combination with HBpin under mild conditions. Arylalkynes featuring electron-withdrawing, electron-donating, and heteroaryl substituents yielded good to excellent results. Thorough DFT calculations were performed to understand the mechanism.